(untitled) (World Bulletin of Education and Learning, 2026)
This article is devoted to studying the role of youth activism and innovative pedagogical approaches in shaping a legal and democratic society. The study analyzes ways to encourage social activity among young people in the pedagogical process, teach them to value legal awareness and democratic principles, and enhance educational effectiveness through innovative methods. The article highlights the importance of strengthening youth participation in social life, developing critical thinking and responsible decision-making skills, and applying innovative tools in the pedagogical process.